Battling a killer cattle disease - International Livestock Research Institute (International Livestock Research Institute, 2011)
Trypanosomiasis is a wasting disease of livestock that maims and eventually kills millions of cattle in Africa and costs farmers billions of dollars annually. In 2011, a group of geneticists at the International Livestock Research Institute in Nairobi, Kenya, and other institutes in the UK identified two genes that enable Africa's ancient N'Dama cattle breed to resist development of the disease trypanosomiasis when infected with the causative, trypanosome, parasite. The team members were able to make use of the latest gene mapping and genomic technologies because they had the genetic systems and experimental populations of livestock in place to do so as these technologies came on stream. Eventually, these results should make it easier for livestock breeders in Africa to breed animals that will remain healthy and productive in areas infested by the disease-carrying tsetse fly. The international team that came together in this project is an example of the disciplinary breadth as well as agility needed to do frontline biology today. In this work, the team developed several new research approaches and technologies that were needed to unravel some fundamental biological issues, with likely benefits for many African farmers and herders.